Keanekaragaman Serangga Pengunjung Tanaman Cabai Rawit (Capsicum annuum L.) di Wiyoro, Bantul - ichsan luqmana Indra Putra (Al-Hayat: Journal of Biology and Applied Biology, 2020)
Chili is one of the plants that’s planted Indonesian. Excessive use of chemical insecticides in chili planters can cause damage to ecosystems for example reducing in biodiversity. This study aims to determine the diversity and abundance of insects found in chili plants in Banguntapan, Bantul. Sampling uses indirect capture, insect nets, yellow pan traps (YPT), and pitfalls. Insect nets were swung along vertically in chili beds. 15 pieces of YPT and pitfalls were installed for each trap. Sampling was done 8 times in 2 months. The results were order that had most species was Hymenoptera (83 species), while the least were Blattaria, Dermaptera, Diplura, Strepsiptera, and Trombidiformes, each 1 species. The order that has the most abundance individuals was Diptera with 2939 individuals. The species that has the highest abundance was Paratrechina longicornis (Hym: Formicidae) with 1071 individuals. The Shanon-Wiener Index value obtained is 1.883621, which classified as medium diversity.